الضوابط اللغوية في التفسير العلمي للقرآن الكريم: Linguistic Rules for the Scientific Interpretation of the Holy Quran - Hafiz Asadullah, asadulah; Hafiz Zulfiqar Shah, hafizulfiqar (Al Manhal Research Journal, 2021)
This Subject of Scientific Interpretation of the Holy Quran is the very significant topic for the young generation & contemporary world. The Quran severally challenges the mankind that it is not composed by any human but it is the very words of Almighty, the Glorified and Exalted. It revealed to the Prophet PBUH and transmitted to us through an authentic and continuous narration without doubt. This Subject of Scientific Interpretation of the Holy Quran is the very significant topic for the young generation & contemporary world. Moreover, this is an remarkable way to show the miracle of the Holy Quran in this world by discussing the Scientific Phenomenon and accuracy of its verses. Therefore, it is recognized the need to establish rules for interpreting the Quran in order to preserve its meaning and protect it form being misinterpreted particular in scientific interpretation of the Holy Quran. This article tried to set these linguistic rules for the interpretation of the Holy Quran. The method used for this research was descriptive and applied.